Considerations for the clinical development of immuno-oncology agents in cancer - Pandiella, Atanasio; Calvo, Emiliano; Moreno, Victor; Amir, Eitan; Templeton, Arnoud; Ocana, Alberto (Frontiers in Immunology, 2023)
Targeting of the immune system has shown to be a successful therapeutic approach in cancer, with the development of check point inhibitors (ICI) or T-cell engagers (TCE). As immuno-oncology agents modulate the immune system to attack cancer cells and do not act directly on oncogenic vulnerabilities, specific characteristics of these compounds should be taken in consideration during clinical development. In this review we will discuss relevant concepts including limitations of preclinical models, special pharmacologic boundaries, clinical development strategies such as the selection of clinical indication, line of treatment and backbone partner, as well as the endpoints and expected magnitude of benefit required at different stages of the drug development. In addition, future directions for early and late trial designs will be reviewed. Examples from approved drugs or those currently in clinical development will be discussed and options to overcome these limitations will be provided.